Targeted transcranial direct current stimulation for rehabilitation after stroke - Dmochowski, Jacek P.; Datta, Abhishek; Huang, Yu; Richardson, Jessica D.; Bikson, Marom; Fridriksson, Julius; Parra, Lucas C. (NeuroImage (Orlando, Fla.), 2013)
Transcranial direct current stimulation (tDCS) is being investigated as an adjunctive technique to behavioral rehabilitation treatment after stroke. The conventional “dosage”, consisting of a large (25cm2) anode over the target with the cathode over the contralateral hemisphere, has been previously shown to yield broadly distributed electric fields whose intensities at the target region are less than maximal. Here, we report the results of a systematic targeting procedure with small “high-definition” electrodes that was used in preparation for a pilot study on 8 stroke patients with chronic aphasia. We employ functional and anatomical magnetic resonance imagery (fMRI/MRI) to define a target and optimize (with respect to the electric field magnitude at the target) the electrode configuration, respectively, and demonstrate that electric field strengths in targeted cortex can be substantially increased (63%) over the conventional approach. The optimal montage exhibits significant variation across subjects as well as when perturbing the target location within a subject. However, for each displacement of the target co-ordinates, the algorithm is able to determine a montage which delivers a consistent amount of current to that location. These results demonstrate that MRI-based models of current flow yield maximal stimulation of target structures, and as such, may aid in reliably assessing the efficacy of tDCS in neuro-rehabilitation. •An optimization algorithm which maximizes current flow at the target is derived.•Electric field intensities at the target are increased by 63%.•Optimized electric field strength is robust to perturbations of the target location.